2018
DOI: 10.1007/s40333-018-0019-9
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungi ameliorate the chemical properties and enzyme activities of rhizosphere soil in reclaimed mining subsidence in northwestern China

Abstract: In semi-arid region of northwestern China, underground mining subsidence often results in decreased vegetation coverage, impoverishment of soil fertility and water stress. In addition, the physical-chemical and biological properties of soil also change, resulting in more susceptible to degradation. In particular, subsidence causes disturbance of the symbioses of plant and microbe that can play a beneficial role in the establishment of vegetation communities in degraded ecosystems. The objective of this study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 56 publications
2
16
0
1
Order By: Relevance
“…Total nitrogen, phosphorus and potassium in leaves, stems and roots were significantly higher in the mycorrhizal plants than the controls (Table 6). These results are similar to those of Qiu et al (2019) and indicate that AMF increased plant nutrient uptake to promote growth.…”
Section: Effect Of Amf Treatment On Plant Nutrient Contentsupporting
confidence: 85%
See 1 more Smart Citation
“…Total nitrogen, phosphorus and potassium in leaves, stems and roots were significantly higher in the mycorrhizal plants than the controls (Table 6). These results are similar to those of Qiu et al (2019) and indicate that AMF increased plant nutrient uptake to promote growth.…”
Section: Effect Of Amf Treatment On Plant Nutrient Contentsupporting
confidence: 85%
“…They can form potentially symbiotic associations with most flowering plant species and have the potential to promote plant growth and to increase net photosynthetic rate [8][9] [10]. AMF can effectively increase plant photosynthetic rate and leaf transpiration, thereby enhancing host plant carbohydrate content and significantly promoting plant yield and biomass [11]. AMF may increase plant photosynthesis, leaf area and chlorophyll content so as to increase plant biomass through various mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…These beneficial microorganisms, by changing the composition and quantity of root exudates, affect the development and activity of soil microorganisms [21]. Mycorrhiza causes changes in the quantity and quality of root exudates [23,43]. Soil enzyme activity was shown to directly affect the available nutrient content in the rhizospheric soil [44], which, in turn, provided soil microbes to increase the enzyme activities of the soil [15].…”
Section: Discussionmentioning
confidence: 99%
“…To better understand soil physical quality before and after mining and during reclamation process, numerous studies have been conducted in past few decades. They include the study on the bulk density, pore size distribution and saturated hydraulic conductivity in Krümmelbein and Raab (2012), the hydrological response of reclaimed mining soils in Heras et al (2009), the temporal availability and spatial distribution of soil moisture in Heras et al (2011), the in ltration rate at reclaimed surface coal mines (Reynolds and Reddy 2012), the soil moisture and groundwater table in Shendong coal mining (Bian et al 2009), the effect on soil physical quality indices (Yang et al 2016), vegetation and environmental patterns (Yang et al 2018) and soil nitrogen (Yang et al 2019) induced by land subsidence, the chemical properties and enzyme activities of rhizosphere ameliorated by Arbuscular mycorrhizal fungi (Qiu et al 2019), the soil enzyme activities and microbial biomass by re-vegetation type and arbuscular mycorrhizal fungal inoculation (Xiao et al 2019) and the spatial and temporal variations of SWC in semi-arid mining area (Wang et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These in uences can be restored through land reclamation and ecological restoration measures, which have been proved to be an effective way to restore the destructive environment in mining areas (Heras et al 2011, Krümmelbein and Raab 2012, Mukhopadhyay et al 2013, Qiu et al 2019, Xiao et al 2019). Land subsidence, as one of the signi cant in uences by underground coal mining, will not only change soil quality but also cause many other eco-environmental problems (Huang et al 2014, Kuter et al 2014, Qiu et al 2019, Wang et al 2017, Yang et al 2016, Yang et al 2018, Yang et al 2019). Statistics showed that 10,000 tons raw coal production would averagely lead to 0.2 hectares subsided lands in China (Bian et al 2010).…”
Section: Introductionmentioning
confidence: 99%